Influence of Magnetic Field on the Electrodeposition and Capacitive Performances of MnO2 - Aldo Girimonte; Andrea Stefani; Massimo Innocenti; Claudio Fontanesi; Roberto Giovanardi (Magnetochemistry, 2021)
This study focuses on the influence of an applied external magnetic field on the electrodeposition process and capacitive performances of MnO<semantics>2</semantics>, as pseudo-capacitive active material for supercapacitors electrodes. MnO<semantics>2</semantics> was electrochemically deposited on Si/Au substrates in the presence and in the absence of a 0.5 T magnet, and its capacitive performance was tested via electrochemical characterization. The samples obtained in the presence of the magnetic field show a positive influence on the deposition process: the increase in deposition efficiency leads to more compact and uniform MnO<semantics>2</semantics> coatings, with a decrease in capacitance values for the samples produced with the magnetic field.